Konsep Tabanni (Pengangkatan Anak) dalam Islam: Antara tradisi dan ketentuan syariah - Faizah, Nur; Umam, M. Shaiful (AL-MUQARANAH, 2025)
The practice of child adoption (Tabanni ) in Indonesia still poses problems due to differences between community traditions, Sharia provisions, and positive legal regulations. Some communities treat adopted children as biological children, including in terms of lineage and inheritance, even though Sharia law stipulates that adoption cannot erase blood ties with biological parents. This study aims to analyze the concept of tabannī in Islam, examine positive legal regulations, and identify practical implications and gaps between legal norms and social practices. The research method used is qualitative with a normative-empirical approach (socio-legal research). Data were obtained through literature studies, legal document analysis, and review of previous studies. The analysis was conducted using the ijtihad maqasidi approach to examine the compatibility of Tabanni  practices with sharia objectives and compare them with social realities in society. The results of the study show that Tabanni  in Islam is limited to the aspect of child maintenance without changing lineage, inheritance rights, or marriage guardian status. Indonesian positive law through the Child Protection Law, Government Regulation No. 54 of 2007, and the Compilation of Islamic Law affirms that adopted children still have a blood relationship with their biological parents and only acquire property through grants or mandatory wills. However, social practices often equate adopted children with biological children, thereby giving rise to legal uncertainty, inheritance disputes, and other issues.